Absolute and relative lymphocyte counts in dengue infection - Bambang Ardianto Bambang Ardianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Dengue infection is one of Indonesia's health problems. Lymphocytes are thought to be involved in dengue pathogenesis.Objectives: To determine whether there were any differences on absolute and relative lymphocyte counts between dengue and non-dengue febrile patients and among dengue fever (DF), dengue hemorrhagic fever without shock (DHFï€´, dengue shock syndrome (DSS), and non-dengue (ND) patients.Methods: A cross-sectional study was conducted on dengue and non-dengue patients hospitalized at "Empat Lima" Hospital, Yogyakarta, during the period of November 23, 2001-January 22, 2002. The diagnosis of dengue infection was confirmed by HI test. Absolute and relative lymphocyte counts were obtained from serial peripheral blood films stained with Giemsa's staining.Results: Thirty-eight DF, 10 DHF, 16 DSS, and 86 ND patients were involved in this study. Absolute and relative counts of each degree were compared each other from the third day until the eighth day after the onset of fever. Absolute lymphocyte counts of dengue patients were higher than those of non-dengue patients on day 5 (p=0.047) and 6 (p =0.022). Absolute lymphocyte counts of DHF patients were higher than those of DF, DSS, and ND patients on day 5 (DF vs. DHF, p =0.003; DHF vs. DSS, p=0.001; ND vs. DHF, p(0.001).Absolute lymphocyte counts of DHF patiens were higher than those of ND patiens on day 6(p=0.018).Relative lymphocyte counts of Df patiens were higher than those of DSSpatiens on day 6(p=0.023), while relative lymphocyte counts of ND patiens were higher than those of DSS patiens on day 7 (p=0.026).Conclution:there were significant differences in absolute lymphocyte counts between dengue and nondengue patiens, DF and DSS patiens, and ND and DSS patiens.Key words:lymphocyte count, dengue infection, dengue shock syndrome, non-dengue infection